2017
DOI: 10.3390/molecules22091420
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of LEDs’ Effects on the Production of Bioactive Compounds and Crop Quality

Abstract: Light-emitting diodes (LEDs) are characterized by their narrow-spectrum, non-thermal photon emission, greater longevity, and energy-saving characteristics, which are better than traditional light sources. LEDs thus hold the potential to revolutionize horticulture lighting technology for crop production, protection, and preservation. Exposure to different LED wavelengths can induce the synthesis of bioactive compounds and antioxidants, which in turn can improve the nutritional quality of horticultural crops. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
118
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(138 citation statements)
references
References 81 publications
(111 reference statements)
1
118
0
6
Order By: Relevance
“…Homogeneous and sufficient illumination and dissipation of the heat for photoauto- and photomixotroph plant cell cultures in the bioreactor are also required. However, demands in terms of the tolerable oxygen transfer rate as well as power input and the intensity (80.7–1345 μmol m −2 s −1 ) and duration (0, 8, 16, 24 h) of illumination may differ for cell growth and product formation (Chattopadhyay et al 2002 ; Eibl et al 2009a ; Hasan et al 2017 ). Werner et al ( 2017 ) propose selecting the bioreactor type depending on the most suitable volumetric oxygen transfer coefficient (k L a) to specific power input (P/V) ratio in a first step.…”
Section: Plant Cell Culture Propagation and Extract Manufacturementioning
confidence: 99%
“…Homogeneous and sufficient illumination and dissipation of the heat for photoauto- and photomixotroph plant cell cultures in the bioreactor are also required. However, demands in terms of the tolerable oxygen transfer rate as well as power input and the intensity (80.7–1345 μmol m −2 s −1 ) and duration (0, 8, 16, 24 h) of illumination may differ for cell growth and product formation (Chattopadhyay et al 2002 ; Eibl et al 2009a ; Hasan et al 2017 ). Werner et al ( 2017 ) propose selecting the bioreactor type depending on the most suitable volumetric oxygen transfer coefficient (k L a) to specific power input (P/V) ratio in a first step.…”
Section: Plant Cell Culture Propagation and Extract Manufacturementioning
confidence: 99%
“…Conventional light sources (fluorescent, metal halide and high‐pressure sodium lamps) have been used in horticultural cultivation, but there are limits in their ability to control light quality and they generate excessive heat, which may cause undesirable effects on plant growth and development 2 . The development of light‐emitting diodes (LEDs) contributes to sufficient uniform lighting to plants and leads to more economic efficiency in controlled environments due to their specific wavelengths, small size, durability, long lifetime and cool emitting temperature 3,4 . Recently, many studies have shown a positive effect of LEDs on plant growth and bioactive compound accumulation in crops and medicinal plants such as lettuce, spinach, kale, basil, sweet pepper, ice plants, rapeseed rosette leaves and Crepidiastrum denticulatum 5–9 …”
Section: Introductionmentioning
confidence: 99%
“…Plant secondary metabolites play significant roles in plants' survival from biotic or abiotic stresses. The antioxidant capability of such metabolites are also believed to benefit human health when consumed (Hasan et al, 2017). Recently, microgreens have become a unique sub-class of high-value fresh baby green vegetables that are readily harvested in 12-14 days.…”
Section: Introductionmentioning
confidence: 99%